Recognizing the first ecological designers: weaving indigenous narratives into landscape architecture curriculum - Leach, Sabreena (Kansas State University, 2024)
Indigenous environmental stewardship, including the realms of Traditional Ecological Knowledge (TEK) and Traditional Ecological Practices (TEP), has gained increasing attention in Western practice in recent years. Indigenous communities possess valuable knowledge and perspectives that can inform the fields of ecological planning and design. However, many Indigenous groups have faced prejudice and targeted cultural dismemberment from the same societies that now wish to learn from them. This research explores how Indigenous narratives can be respectfully told in American landscape architecture curricula. This report compiles key resources and considerations for faculty interested in embarking on this effort. The goal of this research is to encourage better understanding in landscape architecture of contemporary Indigenous communities and their story in relation to the American landscape. To determine what an Indigenous narrative would consist of in curricula, interviews were conducted with practitioners and educators of both Indigenous and non-Indigenous backgrounds who have worked with and learned from Indigenous communities. Interviewees were asked about what key concepts should be covered, how information could be respectfully taught, and how Indigenous communities could be equitably engaged. Responses guided the development of a curriculum framework that explores how content could be interwoven into landscape architecture courses, offering numerous lessons regarding history, worldviews, ethics, ecological design, and community engagement. Indigenous narratives in landscape architecture curricula must transcend historical and contemporary timelines, educating students on injustices while highlighting the cultural strength and knowledge of Indigenous communities. By incorporating an Indigenous narrative into curricula, the profession can recognize the design knowledge of Indigenous communities, think beyond Western worldviews, and engage in informed dialogue with Tribal Nations. The end goal of this initiative is to establish essential understandings in the profession from which long-term relationships with Indigenous communities can be built.
Keywords: Traditional ecological knowledge; Traditional ecological practices; Ecological design; Design education; Equitable partnerships; Curriculum framework